Listening Tasks - Schecter, Sandra (Cambridge University Press, 1984)
Listening Tasks is designed for students who need to understand authentic American English, spoken at normal speed in everyday situations. In the Student's Book, many practical topics, such as calling about an apartment, catching a plane, and finding out what's going on in town, make the material interesting and motivating